2016
DOI: 10.5230/jgc.2016.16.4.230
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Quality of Life after Total Gastrectomy Compared with Partial Gastrectomy: Longitudinal Evaluation by European Organization for Research and Treatment of Cancer-OG25 and STO22

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/ licenses/by-nc/4.0) which permits unrestricted noncommercial use, distribution, and reproduction in any medium, provided the original work is properly cited. IntroductionGastric cancer is one of the most common malignancies worldwide, being the fourth most common cancer and the second leading cause of cancer-related death.1,2 In Korea, gastric cancer is the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Among the identified studies, five were systematic literature reviews [6367], nine were economic analyses [18, 20, 24, 26, 33, 37, 41, 42, 68], six were randomised controlled trials [6973], one was an observational study [74], seven were prospective cohort or case-control studies [39, 7580], seven were cross-sectional survey studies [8187], four were retrospective studies [8891] and one included a retrospective analysis and a prospective cross-sectional survey [92]. Only four studies used tools specific to GC or GEJC (GC module [STO22] and oesophago-gastric [OG25] modules of European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire [EORTC-QLQ]) to assess HRQoL [78, 80, 86, 87]. Among all studies reporting humanistic data ( n = 40), EORTC-QLQ-C30 was the most frequently used cancer-specific tool to assess HRQoL ( n = 13) [39, 64, 6972, 7478, 87, 91].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the identified studies, five were systematic literature reviews [6367], nine were economic analyses [18, 20, 24, 26, 33, 37, 41, 42, 68], six were randomised controlled trials [6973], one was an observational study [74], seven were prospective cohort or case-control studies [39, 7580], seven were cross-sectional survey studies [8187], four were retrospective studies [8891] and one included a retrospective analysis and a prospective cross-sectional survey [92]. Only four studies used tools specific to GC or GEJC (GC module [STO22] and oesophago-gastric [OG25] modules of European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire [EORTC-QLQ]) to assess HRQoL [78, 80, 86, 87]. Among all studies reporting humanistic data ( n = 40), EORTC-QLQ-C30 was the most frequently used cancer-specific tool to assess HRQoL ( n = 13) [39, 64, 6972, 7478, 87, 91].…”
Section: Resultsmentioning
confidence: 99%
“…One study compared the accuracy of the oesophageal cancer-specific scale, EORTC-QLQ-OG25, with the GC-specific scale, EORTC-QLQ-STO22, for the assessment of the HRQoL in patients who underwent partial and total gastrectomy and found that the OG25 was more sensitive than the STO22. In this study, differences between the total and partial gastrectomy groups in weight loss, odynophagia, choking when swallowing and difficulty eating were identified only with the OG25 scale [80], and the OG25 scores for body image, dysphagia, odynophagia, pain and discomfort, anxiety and weight loss were worse after total compared with partial gastrectomy [80].…”
Section: Resultsmentioning
confidence: 99%
“…The Korean version of the EORTC QLQ-C30 was validated in 2004 and has been widely used in postoperative patient surveys [ 8 ]. Various comparative studies have been conducted using these indicators for QOL [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-STO22) and the Functional Assessment of Cancer Therapy-gastric (FACT-Ga) are commonly known instruments [3,4]. The EORTC QLQ-STO22 has been translated into many languages, including Korean, and has been used in many clinical trials and retrospective studies of Korean patients with gastric cancer [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%